INFLUENCE, MOTIVATION, WORK ENVIRONMENT AND DISCIPLINE PERFORMANCE AGAINST HIGH SCHOOL TEACHER IN THE CITY IN BOGOR - Jurnal Ilmiah Manajemen UPB (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2017)
This study aims to determine the effect, motivation, work environment and discipline on the performance of high school teachers in the city of Bogor. This study uses the data questionnaire distributed to teachers working in secondary schools in the city of Bogor. The method used in this research is the analysis of individual level. The research object High School in the city of Bogor. Number of questionnaires distributed as many as 350 sheets, questionnaires back as much as 300 sheets, while a questionnaire that can be used as many as 280 sheets. The test results are used by multiple linear regression which include validity, reliability and test R Square. Results from the study showed the coefficient of determination (adjusted R2) has a value of 0.769, so it can be seen that the variables of motivation, work environment and discipline 78.9%, the performance of teachers of vocational schools in the city of Bogor. while the remaining amount. 21.1% influenced by other factors.